The Effect of Financial Performance on The Value of Companies in The Banking Sector: The Role of Good Corporate Governance as a Moderation Variable - Panca Putra Kusuma, Riky; Widiyanti, Marlina; Malinda, Shelfi; Adam, Mohamad (Pusat Publikasi Nusantara, 2023)
The purpose of this study is to obtain empirical evidence of the influence of profitability (Return On Assets and Return On Equity), BOPO, Credit Risk (NPL ratio) and the role of Good Corporate Governance as a moderating variable on the Value of Banking Companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 13 companies with a research period from 2017-2021 so that there were 65 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple linear regression analysis method with interaction test. The results showed that ROA has a significant positive effect, ROE has a significant negative effect on firm value. Meanwhile, BOPO, NPL and GCG have no effect on company value. GCG as a moderating variable moderates ROE on firm value however, it cannot moderate the effect of ROA, BOPO and NPL. The implication of this research is that companies must pay attention to profitability and those that can affect stock prices so that company value can increase.